Reconstruction of Repetitive Signals - Schijvenaars, R. J. A.; Kors, J. A.; van Bemmel, J. H. (Methods of Information in Medicine, 1994)
A technique is presented for the reconstruction of signals that suffered sampling-frequency decimation. Two assumptions are made: the original signal has to be repetitive, and no anti-aliasing filter has been used before frequency decimation. The performance of the technique is assessed by using test signals of which the original signal is known.
Keywords: Signal Reconstruction; Event Detection; Estimation.